Laser studies of chemical dynamics - Gilchrist, A; Alexander Gilchrist (2013)
In this thesis, resonance enhanced multiphoton ionisation (REMPI) in combination with time-of-flight mass spectrometry (TOF-MS) has been used to detect nascent photofragments resulting from the UV dissociation of a variety of small molecules. The translational anisotropy and angular momentum polarisation of these photofragments has been measured and used to elucidate the underlying photodissociation dynamics. Firstly, the photodissociation of NO2 at 320nm has been investigated and the vector correlations of the nascent NO photofragments have been measured in terms of a set of semi-classical bipolar moments. The measured angular momentum alignment is found to be consistent with an impulsive model for the dissociation, with μ and ν in the same molecular plane and both preferentially perpendicular to J, whilst angular momentum orientation measurements provide evidence for an additional torque due to the O-N-O bond opening during dissociation. These measurements were taken using a rotationally cooled, skimmed molecular beam and significant deviations were found between the bipolar moments measured using this source and previous measurements using a rotationally hotter source. The effect of parent molecular rotations on the measured bipolar moments has been quantified and successfully used to explain these deviations. The photodissociation of Cl2 has been studied in the wavelength region (320-350)nm. UV absorption in this wavelength region may result in two dissociation channels, (Cl+Cl) and (Cl+Cl*), and the angular momentum polarisation of both the Cl(2P3/2) and Cl*(2P1/2) photofragments has been measured. This angular momentum polarisation has been reported in terms of a polarisation parameter formalism which, together with the measured translational anisotropies, has been used to determine the different potential energy surfaces contributing to the dissociation process. Translational anisotropy measurements of the Cl(2P3/2) fragments have shown that, for the ground-state channel, dissociation results from a pure perpendicular transition to the C state, whilst alignment measurements show that non-adiabatic transitions to the A state are significant at large internuclear separations. The measured alignment parameters are found to be relatively constant for all dissociation wavelengths and are consistent with theoretical predictions. Translational anisotropy measurements of the Cl(2P_1/2) photofragments show that, for the excited-state channel, dissociation occurs following a mixed parallel and perpendicular excitation to the B and C states respectively and the interference between these two dissociation pathways has been shown to result in angular momentum orientation. The predissociation dynamics of the C 3Πg (ν=0) and (ν=1) Rydberg states of O2 has been extensively studied. The translational anisotropy and angular momentum alignment of the O(3P) and O(1D) photofragments resulting from this predissociation has been measured in terms of a polarisation parameter formalism, which has been extended for a two-photon dissociation process. Measurements have been taken at various fixed wavelengths within the two bands in order to investigate the differences in the predissociation dynamics of intermediate levels with different values of |Ω|(=0,1,2 in this case). The translational anisotropy is found to be dependent on the dissociation wavelength with the variations found to be consistent with rotational depolarisation due to the long lifetime of the excited C state. All photofragments have been found to be aligned, with the relationship between the measured O(3P) and O(1D) alignment being found to be consistent with a diabatic model of the dissociation. In addition, all photofragments are found to display coherent orientation resulting from interference between two possible two-photon absorption pathways. The measured orientation is affected by rotational depolarisation due to the long lifetime of the excited C state; once this effect is accounted for the orientation is found to be nearly constant over all dissociation wavelengths. The origin of the coherent orientation is attributed to two-photon absorption to different spin-orbit components of the C state.